Cavitary pulmonary Kaposi's sarcoma in AIDS. (2021) - Yano, Shungo; Fukui, Sayato; Inui, Akihiro; Naito, Toshio
Abstract: Many different pulmonary diseases occur in human immunodeficiency virus-infected patients. This was a case of a cavity lesion, although differentiation was extremely difficult pictorially. This was a rare case that led to a definitive diagnosis because the cavity lesions were complicated by pneumothorax, and we could perform a biopsy.